Extreme Sensitivity and the Practical Implications of Risk Assessment Thresholds - John Bukowski DVM, PhD; Mark Nicolich PhD; R. Jeffrey Lewis PhD (SAGE Publishing, 2013)
Traditional risk-assessment theory assumes the existence of a threshold for non-cancer health effects. However, a recent trend in environmental regulation rejects this assumption in favor of non-threshold linearity for these endpoints. This trend is driven largely by two related concepts: (1) a theoretical assumption of wide-ranging human sensitivity, and (2) inability to detect thresholds in epidemiologic models. Wide-ranging sensitivity assumes a subpopulation with extreme background vulnerability, so that even trivial environmental exposures are hazardous to someone somewhere. We use examples from the real world of clinical medicine to show that this theoretical assumption is inconsistent with the biology of mammalian systems and the realities of patient care. Using examples from particulate-matter air-pollution research, we further show that failure to reject linearity is usually driven by statistical rather than biological considerations, and that nonlinear/threshold models often have a similar or better fit than their linear counterparts. This evidence suggests the existence of practical, real-world thresholds for most chemical exposures.